Clean Water Management in Settlements Around the Gebe Island Mine as an Effort for Sustainable Environmental Education - Madi, Usba; M.Taher, Dharmawaty; Sahil, Jailan (JURNAL BIOEDUKASI, 2025)
This study is motivated by the fact that the limited availability of clean water in residential areas around the Gebe Island nickel mine has the potential to cause health risks and environmental degradation due to nickel mining activities in residential areas. This occurs due to the lack of a sustainable education strategy, so a scientific approach is needed in clean water management based on community participation. This study aims to analyze the relationship between environmental education and clean water management based on community empowerment to improve the quality of life and the resilience of water ecosystems in a sustainable manner. This research was conducted using a mixed-method approach. Data were collected through questionnaires, interviews, pretest-posttest and FGD, while data analysis was carried out quantitatively and qualitatively. The results of the research and environmental education training were able to improve community knowledge and behavior in maintaining water quality. The success of this program was influenced by social, economic, and institutional factors as well as the synergy between the government, community and companies in creating a participatory and sustainable water management system.